Main barriers and possible enablers of academicians while publishing - Aydin, Abdulkerim; Yuruk, Suleyman Eren; Reisoglu, Ilknur; Goktas, Yuksel (Springer, 2023)
This study aims to determine the cognitive, social, physical, and affective barriers that prevent academics from publishing and the enablers suggested to overcome these barriers. The study, using the phenomenological research method, involved semi-structured interviews conducted with 41 academicians differing in gender, branch, age, and experience. The deductive analysis of the obtained data showed that the academicians had cognitive difficulties especially in writing the IMRAD sections and writing in English. Their social barriers were found to include the difficulty of journal evaluation processes, the problems experienced in carrying out collaborative studies, and educational, administrative, and family responsibilities. The physical barriers included problems about time management, data collection process, and infrastructure. Lastly, the main affective barriers were not being in the right mood for writing, thinking that studies do not contribute to real life, fear of rejection, lack of self-confidence, and perfectionism. The academicians suggested various enablers, such as finding a good research topic, improving one's English language skills, cooperating, and insisting on acceptance.
Keywords: Barriers to writing; Motivation to write; Writer's block; Writing enablers; Writing for publication; Academic writing